The challenges of implementing ADHD clinical guidelines and research best evidence in routine clinical care settings: a Delphi survey and mixed-methods study - Hall, Charlotte L.; Taylor, John; Newell, Karen; Baldwin, Laurence; Sayal, Kapil; Hollis, Chris (Royal College of Psychiatrists, 2016)
Background The landmark US Multimodal Treatment of ADHD (MTA) study established the benefits of individualised medication titration and optimisation strategies to improve short- to medium-term outcomes in attention-deficit hyperactivity disorder (ADHD). This individualised medication management approach was subsequently incorporated into the National Institute for Health and Care Excellence (NICE) ADHD Clinical Guidelines (NICE CG78). However, little is known about clinicians’ attitudes towards implementing these medication management strategies for ADHD in routine care.